International Criminal Court Jurisdiction Against Human Rights Violations by Philippine President After Withdrawal from Rome Statute (Semarang State University Undergraduate Law and Society Review, 2023)
Rodrigo Duterte who has ordered the police to execute drug addicts who do not want to be arrested. However, the assailant was still shot despite surrendering to arrest, the police on behalf of the anti-drug unit went to people's homes and did so because of the policy of "who gets killed, the police get paid". The crime that has been committed by Rodrigo Duterte under ICC jurisdiction is giving orders. to the police and the public to carry out extrajudicial killings of individuals involved in narcotics and to protect those who carry out their orders, so that Rodrigo Duterte is judged guilty and responsible in accordance with Article 25 paragraph 3 (b), (c), (d) the Rome Statute Crimes against humanity are among the criminal jurisdictions of the ICC. Although the Philippines withdrew from the Rome Statute, it did not prevent the International Criminal Court (ICC) from reviewing the case involving Philippine President Rodrigo Duterte. The Rome Statute provides for withdrawals, in particular article 127 , paragraphs (1) and (2) of the 1998 Rome Statute.